Midnight and other stories - Tate, Socorro Federis (Ateneo de Naga University Press, 2014)
In this collection of stories is the world of Socorro Federis-Tate, in the form of forests that are fast disappearing, of dreaded birds of ill omen all gone, the boy dying not of enchantment but of disenchantment. The outsiders are observed, deconstructed but embraced and loved. Women are barren and die alone or die even when living. Memory plays tricks in the stories of Socorro Federis-Tate because, somehow, in the remembering lessons are learned about a life out there.